Análise do efeito imunomodulador da ouabaína na inflamação e nocicepção - Vasconcelos, Danielle Ingrid Bezerra de (2011)
Ouabain, known as a cardiotonic glycoside capable of inhibiting the Na+/K+ ATPase, was widely used for heart failure treatment. Identified as an endogenous substance, ouabain is capable of interfering with various physiological functions, including immune system modulation. Besides that, little is known about the involvement of this substance in nociceptive and inflammatory processes. The present study investigated the role of ouabain in acute peripheral inflammation induced by intraplantar administrartion of different phlogistic agents (carrageenan, compound 48/80, histamine, bradykinin, and PGE2) and in nociceptive processes (abdominal writhing induced by acetic acid and hot plate). Ouabain produced a significant reduction in the mouse paw edema induced by carrageenan and compound 48/80. This antiinflammatory effect of ouabain is associated to the inhibition of PGE2, bradykinin, and mast-cell degranulation, but not to histamine. Ouabain also presented a central and peripheral anti-nociceptive activity. This analgesic potential might be related to the inhibition of inflammatory mediators and to activation of opioid receptors, since it was reversed by naloxone, an opioid antagonist. Additionally, the analgesic effect of ouabain was not related to sedative effect or to motor function. Taken together, the present work demonstrated for the first time, in vivo, the antiinflammatory and analgesic potential of ouabain